Signal-receiving UAV Positioning Model Based on Geometric Analysis - Li, Yinfeng; Wang, Qisen; Gu, Yongcheng; Zhou, Xintong; Song, Chenming (International Journal of Computer Science and Information Technology, 2024)
A drone is an aerial vehicle without a pilot or controller that is remotely controlled using aerodynamics to fulfil a designated task under certain circumstances. With the encouragement and support of national policies, the development of China’s UAV industry has a good prospect. In real life, location information is the key information for UAVs to accurately complete operations and realise mission requirements, and the importance of its accurate positioning is self-evident. For the UAV localisation model, the bias-free localisation model is established first, and then the localisation model in the case of bias is solved on this basis. When there is a deviation in the received signal UAV, the UAV may be located outside the circle, on the circle, and inside the circle. Specifically divided into four scenarios, see Figure 1-4. (Analysed: outside the circle: θ1’<θ1; inside the circle: θ1’>θ1; circle on the left: θ2>θ2’, right: θ2<θ2’; no deviation: θ1’=θ1, θ2’<θ2). When the position of the passive receiving signal UAV does not exist deviation, according to the position relationship obtained four cases, respectively, the establishment of the quadrilateral, the use of sinusoidal theorem to obtain the receiving signal UAV positioning model, the same can be obtained under the existence of deviation, the specific positioning model of the receiving signal UAV.